Gingipain‐dependent degradation of mammalian target of rapamycin pathway proteins by the periodontal pathogen Porphyromonas gingivalis during invasion. (29th May 2013) - Stafford, P.; Higham, J.; Pinnock, A.; Murdoch, C.; Douglas, C.W.I.; Stafford, G.P.; Lambert, D.W.
Summary: Porphyromonas gingivalis and Tannerella forsythia are gram‐negative pathogens strongly associated with periodontitis. Their abilities to interact, invade and persist within host cells are considered crucial to their pathogenicity, but the mechanisms by which they subvert host defences are not well understood. In this study, we set out to investigate whether P. gingivalis and T. forsythia directly target key signalling molecules that may modulate the host cell phenotype to favour invasion and persistence. Our data identify, for the first time, that P. gingivalis, but not T. forsythia, reduces levels of intracellular mammalian target of rapamycin (mTOR) in oral epithelial cells following invasion over a 4‐h time course, via the action of gingipains. The ability of cytochalasin D to abrogate P. gingivalis‐ mediated mTOR degradation suggests that this effect is dependent upon cellular invasion. We also show that levels of several other proteins in the mTOR signalling pathway are modulated by gingipains, either directly or as a consequence of mTOR degradation including p‐4E‐BP1. Taken together, our data suggest that P. gingivalis manipulates the mTOR pathway, providing evidence for a potentially novel mechanism by which P. gingivalis mediates its effects on host cell responses to infection.